The effect of giving efflurage massage and lavender aroma therapy on the scale of dysmenorrhea pain in young women - LELLY APRILIA VIDAYATI (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2020)
Menstruation is bleeding from the uterus regularly as a sign that the uterine organs are fully functional. Menstruation experienced by adolescents is often accompanied by complaints, namely dysmenorrhoea, dysmenorrhoea can interfere with daily activities. Ideally, young women do not experience dysmenorrhoea during menstruation. From the preliminary results, there are 72% of young women who experience dysmenorrhoea. The purpose of this study was to analyze the effect of giving Effleurage Massage and Lavender Aromatherapy on the scale of dysmenorrhoea pain in adolescent girls at the Darussalam Al-Faisholiyah Islamic Boarding School, Ketapang Sampang. The design used in this study used a Quasy Experiment Design, the independent variables were Effleurage Massage, Lavender Aromatherapy and the dependent variable was the dysmenorrhoea pain scale in adolescent girls. The study population was all young women who experienced dysmenorrhoea pain scale as many as 21 young women and a sample of 10 young women. The sampling technique used is non probability sampling using accidental sampling technique. The statistical test used is the Wilcoxon test. The results of statistical tests using the Wilcoxon test in the Effleurage Massage group obtained a value of p = 0.004, so the p value was less than α = (0.004 <0.05) and the Lavender Aromatherapy group had a value of p = 0.004 <0.05. Then H1 is accepted. Thus it can be concluded that there is an effect before and after the Effleurage Massage and Lavender Aromatherapy techniques are carried out on the scale of dysmenorrhoea pain in young women at the Darussalam Al-Faisoliyah Islamic Boarding School, Ketapang Sampang. The results of this study are suggested for young women who experience dysmenorrhoea pain scale to do Efflerage Massage and Lavender Aromatherapy so as to improve blood circulation during menstruation and be able to carry out daily activities properly.